KARAKTERISTIK GULMA DAN KOMPONEN HASIL TANAMAN PADI SAWAH (Oryza sativa L.) SISTEM SRI PADA WAKTU KEBERADAAN GULMA YANG BERBEDA - Antralina, Merry (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2012)
Rice is an important component of farming in Indonesia, because it is a staplecrop that should be available at all times. Therefore, rice production must be improvedboth intensive and extension. One of the increase in rice yield can be done by adjustingthe cropping system include the SRI (The System of Rice Intensification) . But rice withSRI method resulted weeds growth, because the SRI system, conditioned water withoutflooded. The object of the experiment was to study the characteristics of weeds and yieldcomponents of rice (Oryza sativa L.) on the SRI paddy cultivation due to Presence ofWeed. The design of experiment was a Randomized Block Design with eight treatmentand replicated 3 times. Eight treatments were as follows : A = With weeds to harvest, B =With weeds until the age of 21 days after planting (DAP), C = With weeds until the ageof 42 DAP, D = With weeds until the age of 63 DAP, E = weeds free until the age of 21DAP , F = weeds free until the age of 42 DAP, G = weeds free until the age of 63 DAP,H = weeds free until harvest. The results of this experiment showed that : There arenine species of weeds, which consists of seven dominant species, the 3 species ofbroadleaf groups, two species of grass and two species of seedges groups, Yieldcomponents of paddy crop in the SRI system is influenced by the presence of a weed in aplantation, so that weeding will be done on SRI's cropping system. Control of weeds incropping systems SRI, should be done at the right time, at least until the age of the plant42 days after planting.